2018
DOI: 10.1016/j.cell.2018.05.027
|View full text |Cite
|
Sign up to set email alerts
|

A Milieu Molecule for TGF-β Required for Microglia Function in the Nervous System

Abstract: Extracellular proTGF-β is covalently linked to "milieu" molecules in the matrix or on cell surfaces and is latent until TGF-β is released by integrins. Here, we show that LRRC33 on the surface of microglia functions as a milieu molecule and enables highly localized, integrin-αVβ8-dependent TGF-β activation. Lrrc33 mice lack CNS vascular abnormalities associated with deficiency in TGF-β-activating integrins but have microglia with a reactive phenotype and after 2 months develop ascending paraparesis with loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
164
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(176 citation statements)
references
References 41 publications
12
164
0
Order By: Relevance
“…Previous studies indicated that TGF signaling played vital roles in maintaining microglia homeostasis (Butovsky et al 2014;Qin et al 2018;Zoller et al 2018). Interestingly, we found both the type-1 and type-2 TGFreceptors, which are highly expressed in homeostatic microglia, were notably downregulated after NG2 glia depletion (Fig.…”
Section: Absence Of Ng2 Glia Impairs the Microglia Tgfsignalingmentioning
confidence: 53%
See 1 more Smart Citation
“…Previous studies indicated that TGF signaling played vital roles in maintaining microglia homeostasis (Butovsky et al 2014;Qin et al 2018;Zoller et al 2018). Interestingly, we found both the type-1 and type-2 TGFreceptors, which are highly expressed in homeostatic microglia, were notably downregulated after NG2 glia depletion (Fig.…”
Section: Absence Of Ng2 Glia Impairs the Microglia Tgfsignalingmentioning
confidence: 53%
“…Disrupting TGF signaling in microglia through conditional removal of TGF receptor 2 in the adult brain resulted in loss of microglia homeostasis and altered microglia response to stimulations (Zoller et al 2018). The action of TGFβ on microglia is highly selective and localized, with little spreading between neighboring cells (Qin et al 2018). This process is noncell-autonomous and relies on interactions between microglia and integrin αvβ8-bearing cells in the brain (Qin et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that TGFβ signaling played vital roles in maintaining microglia homeostasis (Butovsky et al, ; Qin et al, ; Zoller et al, ). Interestingly, we found both the Type‐1 and Type‐2 TGFβ receptors, which are highly expressed in homeostatic microglia, were notably downregulated after NG2 glia depletion (Figure e).…”
Section: Resultsmentioning
confidence: 99%
“…Disrupting TGFβ signaling in microglia through conditional removal of TGFβ receptor 2 in the adult brain resulted in loss of microglia homeostasis and altered microglia response to stimulations (Zoller et al, ). The action of TGFβ on microglia is highly selective and localized, with little spreading between neighboring cells (Qin et al, ). This process is non‐cell‐autonomous and relies on interactions between microglia and integrin αvβ8‐bearing cells in the brain (Qin et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation